2022
DOI: 10.3390/pharmaceutics14112372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of Indole-Functionalized Derivatives of Betulin

Abstract: Pentacyclic triterpenes, including betulin, are widespread natural products with various pharmacological effects. These compounds are the starting material for the synthesis of substances with promising anticancer activity. The chemical modification of the betulin scaffold that was carried out as part of the research consisted of introducing the indole moiety at the C-28 position. The synthesized new 28-indole-betulin derivatives were evaluated for anticancer activity against seven human cancer lines (A549, MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Indole-betulin hybrid EB355A (11, half maximal effective concentration/EC 50 : 67 µM) displayed modest efficacy against MCF-7 cancer cells, while betulin displayed no activity (EC 50 : >226 µM), implying that the activity was improved by decorating the botulin with indole at position C-26. [39] Further SARs study demonstrated that (1) esterification of the C-3 positional hydroxyl group of botulin decreased the activity [39] ; (2) EB367 (12, IC 50 :…”
Section: Indole/isatin-steroid Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole-betulin hybrid EB355A (11, half maximal effective concentration/EC 50 : 67 µM) displayed modest efficacy against MCF-7 cancer cells, while betulin displayed no activity (EC 50 : >226 µM), implying that the activity was improved by decorating the botulin with indole at position C-26. [39] Further SARs study demonstrated that (1) esterification of the C-3 positional hydroxyl group of botulin decreased the activity [39] ; (2) EB367 (12, IC 50 :…”
Section: Indole/isatin-steroid Hybridsmentioning
confidence: 99%
“…Indole‐betulin hybrid EB355A ( 11 , half maximal effective concentration/EC 50 : 67 µM) displayed modest efficacy against MCF‐7 cancer cells, while betulin displayed no activity (EC 50 : >226 µM), implying that the activity was improved by decorating the botulin with indole at position C‐26. [ 39 ] Further SARs study demonstrated that (1) esterification of the C‐3 positional hydroxyl group of botulin decreased the activity [ 39 ] ; (2) EB367 ( 12 , IC 50 : 35 µM) demonstrated greater activity against MCF‐7 cancer cells, indicating that moving the indole fragment from the C‐28 to the C‐3 position of the botulin backbone might somewhat boost up activity. [ 40 ] Mechanistically, MCF‐7 cells might be stopped in the G1 phase by EB355A, which also causes apoptotic cell death.…”
Section: Indole/isatin‐steroid Hybridsmentioning
confidence: 99%
“…In the acylation of betulin 1 and 3-acetyl betulin 3a with indolyl acetic acid, derivatives were formed, combining two pharmacophoric fragments in their structure: the betulin skeleton and the heterocyclic indole system, compounds 5a and 5b , respectively ( Figure 8 ) [ 71 ].…”
Section: Synthesis Of Betulin Derivativesmentioning
confidence: 99%
“…Anhydrous dichloromethane was used as the solvent. The cytotoxic activity of the obtained derivatives 5a and 5b was tested on human colorectal adenocarcinoma cells HT-29 and DLD-1 [ 71 ].…”
Section: Synthesis Of Betulin Derivativesmentioning
confidence: 99%
“…Fig. 1 contains the structures and biological significance of some important natural compounds and derivatives of natural compounds ((−)-Herdmanine D 1 , Gallinamide A 2 , Betulin derivative 3 , Leoligin 4 ) [ [19] , [20] , [21] , [22] ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%